THE COMPLEX NARRATIVES OF CONNUBIALITY IN WILLIAM SHAKESPEARE’S THE MERCHANT OF VENICE AND THE TRAGEDY OF OTHELLO THE MOOR OF VENICE - G.M. Adhyanggono (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2012)
The complexity of connubiality in the two plays can be interwoven by many factors. The discussion of the connubiality or marriage in the plays may not be easily separated from issues of racial sentiments and prejudice since both plays are not free from such issues. Therefore, this article highlights the complexity within three aspects: the purpose or the motive of the marriage, the matrimonial ceremony, and the racial prejudice overshadowing it. Making use of narrative study and documentary analysis, this article closely studies the existence and inter-relation of those three aspects in order to better comprehend the plays. The results show that the aspects of motive and as well as racial sentiments and prejudice are present in both plays while aspect of matrimonial ceremony is not clearly present. It is because of this amalgam that makes the plays more aesthetic from narrative standpoint.